The importance of local community safety as the challenge for global security policy - Качала, Тамара Миколаївна; Grzywna, Zbigniew (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2015)
The development of civilization is associated with numerous and complex addictions to produced technique which is destined to fulfill the needs in all fields of everyday life. Such activities may cause a lot of risks at both local and regional level. Globalization is a very wide and complex process, which affects all spheres of life: economic, social, political, etc. Simplifying, it can be considered that globalization is a higher and advanced level of the process of internationalization of economic activity. Undoubtedly, globalization has a great positive or negative impact on the life of every community.